A high-stability and high-performance sodium ion battery positive electrode material and its preparation method and application

By modifying the positive electrode material of sodium ion battery using double-covering method and using NASICON type sodium ion conductor as the coating agent, the shortcomings of existing materials in air stability and rate performance are solved, and higher gram capacity and circulation performance are achieved.

CN119038634BActive Publication Date: 2025-04-08NINGBO VEKEN BATTERY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411538322.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-04-08
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

The existing sodium ion battery positive electrode materials have shortcomings in air stability and rate performance, and improvements often sacrifice performance on the one hand.

Method used

The layered transition metal oxide is coated in situ by double-covering means, and a NASICON type sodium ion conductor with impurities on the surface is used as the coating agent to form an in situ double-covering structure.

Benefits of technology

The air stability and rate performance of the positive electrode material of sodium ion battery is significantly improved, and the capacity and circulation performance are enhanced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention belongs to the technical field of sodium ion battery positive electrode materials, and relates to a high-stability and high-performance sodium ion battery positive electrode material and its preparation method and application. The preparation method comprises the following steps: preparing an NFM sample using a sodium salt and a precursor, and then preparing a sodium ion battery positive electrode material using the NFM sample and a sodium ion conductor. The sodium ion conductor is a NASICON type sodium ion conductor containing impurities M on the surface, and the general formula is M-Na 2+x Zr2Si 3‑x P x O 12 , wherein M is one or more of Zr, Na, and P, and 0<x<3. The present invention innovatively prepares a NASICON-type sodium ion conductor with excessive impurities on the surface, and in-situ coats the layered transition metal oxide by forming a double coating, which effectively improves the air stability and rate performance of the layered transition metal oxide, and exhibits a higher gram capacity and better cycle performance as a positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion battery positive electrode materials, and relates to a high-stability and high-performance sodium ion battery positive electrode material, and a preparation method and application thereof. Background Art

[0002] Sodium-ion batteries are seen as a potential alternative energy storage solution due to their lower cost and similar "rocking chair" storage mechanism to lithium-ion batteries. In a battery system, the design and selection of cathode materials are crucial to improving the overall energy density. Among the many possible cathode material options, layered transition metal oxides have attracted widespread attention due to their high reversible specific capacity and relatively simple synthesis process. This type of material has become a hot topic of research because of its high theoretical specific capacity.

[0003] However, despite their many advantages, layered transition metal oxides also have some significant disadvantages, which limit their potential for practical commercial applications. The main problems include poor air stability and rate performance (i.e., performance at high charge and discharge rates). In addition, due to the structural characteristics of the material itself, such as the small interlayer distance, attempts to improve air stability often come at the expense of rate performance, and vice versa.

[0004] In order to overcome the above problems, a common method in the prior art is to coat the material. The coating material can be various metal oxides, such as boron oxide (B2O3), aluminum oxide (Al2O3) or cobalt oxide (CoO), or a sodium-rich solid electrolyte. However, although such coating treatment can improve the stability of the material to a certain extent, it also brings new challenges, such as the possible reduction of the effective mass of the active material, which in turn affects the overall gram capacity of the battery, and the coating effect is often not ideal.

[0005] Therefore, it is urgent to focus the research work on the cathode materials of sodium-ion batteries on the development of more effective modification technologies, aiming to improve the air stability of layered transition metal oxides while maintaining or even enhancing their rate performance, so as to provide more ideal cathode materials for sodium-ion batteries. These improvements will help promote the maturity of sodium-ion battery technology and ultimately achieve large-scale commercial applications. Summary of the invention

[0006] The present invention aims to solve the problems existing in the prior art of positive electrode materials for sodium ion batteries and provides a highly stable and high-performance positive electrode material for sodium ion batteries and a preparation method and application thereof.

[0007] One object of the present invention is achieved by the following technical solutions:

[0008] A method for preparing a highly stable and high-performance sodium ion battery positive electrode material, the preparation method comprising the following steps:

[0009] (1) The sodium salt and the precursor are mixed and stirred in a solvent, and then the mixture is pre-calcined and high-temperature calcined, and then ground to obtain the NFM sample;

[0010] (2) The NFM sample and the sodium ion conductor are mixed evenly, coated and kept warm at high temperature to obtain the positive electrode material of the sodium ion battery.

[0011] The sodium ion conductor is a NASICON type sodium ion conductor containing impurities M on the surface, and the general formula is M-Na 2+ x Zr2Si 3-x P x O 12 , wherein M is one or more of Zr, Na, P, and 0<x<3.

[0012] Preferably, the impurities M and Na in the sodium ion conductor 2+x Zr2Si 3-x P x O 12 The molar ratio is (0.1-0.5):1. More preferably, it is (0.2-0.4):1.

[0013] Preferably, the preparation method of the sodium ion conductor comprises the following steps: mixing Na2CO3, ZrO2, SiO2 and (NH4)2HPO4 according to the molar ratio in the general formula, sintering at high temperature and then crushing to obtain the sodium ion conductor M-Na 2+ x Zr2Si 3-x P x O 12 .

[0014] In the preparation method of the sodium ion conductor, preferably, the high temperature sintering temperature is 1200-1600° C., and the sintering time is 4-12 hours. More preferably, the high temperature sintering temperature is 1300-1400° C., and the sintering time is 8-10 hours.

[0015] In the method for preparing the sodium ion conductor, preferably, the particle size D50 after crushing is 0.1 to 5 μm, and more preferably 0.1 to 3 μm.

[0016] Preferably, in step (1), the sodium salt includes one or more of sodium acetate, sodium nitrate, sodium acetate, sodium carbonate, sodium oxalate, and sodium carbonate.

[0017] Preferably, in step (1), the general formula of the precursor is [Ni 1-a-b Fea Mn b ]O2, where 0≤a≤1, 0≤b≤1, 0≤a+b≤1.

[0018] Preferably, in step (1), the sodium salt and the precursor are mixed and stirred at a molar ratio of the sodium element in the sodium salt to the precursor of (1-2):1.

[0019] Preferably, in step (1), the solvent is an organic solvent, including one or more of ethanol, NMP, ether, methanol, isopropanol, and tetrahydrofuran.

[0020] Preferably, in step (1), the pre-calcination temperature is 300-600° C., and the pre-calcination time is 1-5 h.

[0021] Preferably, in step (1), the high temperature calcination temperature is 700-900°C, and the high temperature calcination time is 10-24h.

[0022] Preferably, in step (1), the calcination atmosphere for pre-calcination and high-temperature calcination includes one or more of air, oxygen and CO.

[0023] Preferably, in step (2), the molar ratio of the NFM sample to the sodium ion conductor is 1:(0.01-0.1), and more preferably 1:(0.03-0.07).

[0024] Preferably, in step (2), the coating temperature is 600-1000°C, and the insulation time is 10-20 hours. More preferably, the coating temperature is 800-900°C, and the insulation time is 12-18 hours.

[0025] Preferably, in step (2), the coating atmosphere includes one or more of air, oxygen and CO.

[0026] The second object of the present invention is achieved by the following technical solutions:

[0027] A highly stable and high-performance sodium ion battery positive electrode material is prepared by the above-mentioned preparation method.

[0028] The third object of the present invention is achieved by the following technical solutions:

[0029] A highly stable and high-performance sodium ion battery positive electrode plate comprises the above-mentioned highly stable and high-performance sodium ion battery positive electrode material.

[0030] The fourth object of the present invention is achieved by the following technical solutions:

[0031] A high-stability and high-performance sodium ion battery comprises the above-mentioned high-stability and high-performance sodium ion battery positive electrode plate.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] 1. The present invention provides a highly stable and high-performance sodium ion battery positive electrode material, which innovatively adopts a double-coating method to in-situ coat the layered transition metal oxide, effectively improving the air stability and rate performance of the layered transition metal oxide; when used as a sodium ion positive electrode material, it exhibits higher gram capacity and rate performance, as well as better material cycle performance.

[0034] 2. The present invention provides a highly stable and high-performance sodium ion battery positive electrode material, which uses a NASICON type sodium ion conductor with excess impurities on the surface to in-situ coat the sodium ion battery positive electrode material. This coating can use the excess impurities generated on the surface of the NASICON type sodium ion conductor as a coating agent to further coat the sodium positive electrode material to form an in-situ double coating. This double coating method has a better coating effect on the surface of the sodium positive electrode material, showing higher air stability, better rate performance and cycle performance.

[0035] 3. The highly stable and high-performance sodium ion battery positive electrode material provided by the present invention has shown great application potential in the field of sodium ion batteries. It is expected that in future energy storage solutions, this type of sodium ion battery will play an important role and lead the development trend of a new generation of energy storage technology. DETAILED DESCRIPTION

[0036] The technical solution of the present invention is further described below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.

[0037] Example 1

[0038] This embodiment has a high stability and high performance sodium ion battery positive electrode material Zr-Na3Zr2Si2PO 12 The preparation method comprises the following steps:

[0039] (1) Combine Na2CO3, [Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ]O2 was mixed with anhydrous ethanol at a molar ratio of 0.525:1 and stirred evenly, and then the mixture was placed in a tube furnace for pre-calcination at a temperature of 500°C for 5 hours; then high-temperature calcination was performed at a temperature of 850°C for 15 hours, and then the NFM sample was obtained by grinding;

[0040] (2) Na2CO3, ZrO2, SiO2 and (NH4)2HPO4 were mixed in a molar ratio of 1.5:2.3:2:1, and the mixture was placed in a muffle furnace and kept at 1300°C for 8 hours, and then crushed to control the D50 to 3 μm to obtain the sodium ion conductor Zr-Na3Zr2Si2PO 12 ;

[0041] (3) NFM samples and sodium ion conductor Zr-Na3Zr2Si2PO 12 The mixture was mixed evenly at a molar ratio of 1:0.05, and then placed in a tube furnace and calcined at 850°C for coating. The mixture was kept warm for 15 hours to obtain the sodium ion battery positive electrode material Na3Zr2Si2PO 12 @Zr@NFM.

[0042] Example 2

[0043] The preparation method of the high-stability and high-performance sodium ion battery positive electrode material of this embodiment comprises the following steps:

[0044] (1) Combine Na2CO3, [Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ]O2 was mixed with anhydrous ethanol at a molar ratio of 0.525:1 and stirred evenly, and then the mixture was placed in a tube furnace for pre-calcination at 500°C for 5 hours; then high-temperature calcination was performed at 850°C for 15 hours, and then the NFM sample was obtained by grinding;

[0045] (2) Na2CO3, ZrO2, SiO2 and (NH4)2HPO4 were mixed in a molar ratio of 1.5:2.1:2:1, and the mixture was placed in a muffle furnace and kept at 1300°C for 8 hours, and then crushed to control the D50 to 3 μm to obtain the sodium ion conductor Zr-Na3Zr2Si2PO 12 ;

[0046] (3) NFM samples and sodium ion conductor Zr-Na3Zr2Si2PO 12 The mixture was mixed evenly at a molar ratio of 1:0.05, and then placed in a tube furnace and calcined at 850°C for coating. The mixture was kept warm for 15 hours to obtain the sodium ion battery positive electrode material Na3Zr2Si2PO 12 @Zr@NFM.

[0047] Example 3

[0048] The preparation method of the high-stability and high-performance sodium ion battery positive electrode material of this embodiment comprises the following steps:

[0049] (1) Combine Na2CO3, [Ni 1 / 3 Fe 1 / 3 Mn1 / 3 ]O2 was mixed with anhydrous ethanol at a molar ratio of 0.525:1 and stirred evenly, and then the mixture was placed in a tube furnace for pre-calcination at 500°C for 5 hours; then high-temperature calcination was performed at 850°C for 15 hours, and then the NFM sample was obtained by grinding;

[0050] (2) Na2CO3, ZrO2, SiO2 and (NH4)2HPO4 were mixed in a molar ratio of 1.5:2.5:2:1, and the mixture was placed in a muffle furnace and kept at 1300°C for 8 hours, and then crushed to control the D50 to 3 μm to obtain NASICON type sodium ion conductor Zr-Na3Zr2Si2PO 12 ;

[0051] (3) NFM samples and sodium ion conductor Zr-Na3Zr2Si2PO 12 The mixture was mixed evenly at a molar ratio of 1:0.05, and then placed in a tube furnace and calcined at 850°C for coating. The mixture was kept warm for 15 hours to obtain the sodium ion battery positive electrode material Na3Zr2Si2PO 12 @Zr@NFM.

[0052] Example 4

[0053] The preparation method of the high-stability and high-performance sodium ion battery positive electrode material of this embodiment comprises the following steps:

[0054] (1) Combine Na2CO3, [Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ]O2 was mixed with anhydrous ethanol at a molar ratio of 0.525:1 and stirred evenly, and then the mixture was placed in a tube furnace for pre-calcination at 500°C for 5 hours; then high-temperature calcination was performed at 850°C for 15 hours, and then the NFM sample was obtained by grinding;

[0055] (2) Na2CO3, ZrO2, SiO2 and (NH4)2HPO4 were mixed in a molar ratio of 1.5:2.3:2:1, and the mixture was placed in a muffle furnace and kept at 1200°C for 8 hours, and then crushed to control the D50 to 3 μm to obtain NASICON type sodium ion conductor Zr-Na3Zr2Si2PO 12 ;

[0056] (3) NFM samples and sodium ion conductor Zr-Na3Zr2Si2PO 12 The mixture was mixed evenly at a molar ratio of 1:0.05, and then placed in a tube furnace and calcined at 850°C for coating. The mixture was kept warm for 15 hours to obtain the sodium ion battery positive electrode material Na3Zr2Si2PO 12 @Zr@NFM.

[0057] Example 5

[0058] The preparation method of the high-stability and high-performance sodium ion battery positive electrode material of this embodiment comprises the following steps:

[0059] (1) Combine Na2CO3, [Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ]O2 was mixed with anhydrous ethanol at a molar ratio of 0.525:1 and stirred evenly, and then the mixture was placed in a tube furnace for pre-calcination at 500°C for 5 hours; then high-temperature calcination was performed at 850°C for 15 hours, and then the NFM sample was obtained by grinding;

[0060] (2) Na2CO3, ZrO2, SiO2 and (NH4)2HPO4 were mixed in a molar ratio of 1.5:2.3:2:1, and the mixture was placed in a muffle furnace and kept at 1600°C for 8 hours, and then crushed to control the D50 to 3 μm to obtain NASICON type sodium ion conductor Zr-Na3Zr2Si2PO 12 ;

[0061] (3) NFM samples and sodium ion conductor Zr-Na3Zr2Si2PO 12 The mixture was mixed evenly at a molar ratio of 1:0.05, and then placed in a tube furnace and calcined at 850°C for coating. The mixture was kept warm for 15 hours to obtain the sodium ion battery positive electrode material Na3Zr2Si2PO 12 @Zr@NFM.

[0062] Example 6

[0063] The preparation method of the high-stability and high-performance sodium ion battery positive electrode material of this embodiment comprises the following steps:

[0064] (1) Combine Na2CO3, [Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ]O2 was mixed with anhydrous ethanol at a molar ratio of 0.525:1 and stirred evenly, and then the mixture was placed in a tube furnace for pre-calcination at 500°C for 5 hours; then high-temperature calcination was performed at 850°C for 15 hours, and then the NFM sample was obtained by grinding;

[0065] (2) Na2CO3, ZrO2, SiO2 and (NH4)2HPO4 were mixed in a molar ratio of 1.5:2.3:2:1, and the mixture was placed in a muffle furnace and kept at 1300°C for 4 hours, and then crushed to control the D50 to 3 μm to obtain NASICON type sodium ion conductor Zr-Na3Zr2Si2PO 12 ;

[0066] (3) NFM samples and sodium ion conductor Zr-Na3Zr2Si2PO 12 The mixture was mixed evenly at a molar ratio of 1:0.05, and then placed in a tube furnace and calcined at 850°C for coating. The mixture was kept warm for 15 hours to obtain the sodium ion battery positive electrode material Na3Zr2Si2PO 12 @Zr@NFM.

[0067] Example 7

[0068] The preparation method of the high-stability and high-performance sodium ion battery positive electrode material of this embodiment comprises the following steps:

[0069] (1) Combine Na2CO3, [Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ]O2 was mixed with anhydrous ethanol at a molar ratio of 0.525:1 and stirred evenly, and then the mixture was placed in a tube furnace for pre-calcination at 500°C for 5 hours; then high-temperature calcination was performed at 850°C for 15 hours, and then the NFM sample was obtained by grinding;

[0070] (2) Na2CO3, ZrO2, SiO2 and (NH4)2HPO4 were mixed in a molar ratio of 1.5:2.3:2:1, and the mixture was placed in a muffle furnace and kept at 1300°C for 12 hours, and then crushed to control the D50 to 3 μm to obtain NASICON type sodium ion conductor Zr-Na3Zr2Si2PO 12;

[0071] (3) NFM samples and sodium ion conductor Zr-Na3Zr2Si2PO 12 The mixture was mixed evenly at a molar ratio of 1:0.05, and then placed in a tube furnace and calcined at 850°C for coating. The mixture was kept warm for 15 hours to obtain the sodium ion battery positive electrode material Na3Zr2Si2PO 12 @Zr@NFM.

[0072] Example 8

[0073] The preparation method of the high-stability and high-performance sodium ion battery positive electrode material of this embodiment comprises the following steps:

[0074] (1) Combine Na2CO3, [Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ]O2 was mixed with anhydrous ethanol at a molar ratio of 0.525:1 and stirred evenly, and then the mixture was placed in a tube furnace for pre-calcination at 500°C for 5 hours; then high-temperature calcination was performed at 850°C for 15 hours, and then the NFM sample was obtained by grinding;

[0075] (2) Na2CO3, ZrO2, SiO2 and (NH4)2HPO4 were mixed in a molar ratio of 1.5:2.3:2:1, and the mixture was placed in a muffle furnace and kept at 1300°C for 8 hours, and then crushed, and the D50 was controlled to be 1 μm to obtain NASICON type sodium ion conductor Zr-Na3Zr2Si2PO 12 ;

[0076] (3) NFM samples and sodium ion conductor Zr-Na3Zr2Si2PO 12 The mixture was mixed evenly at a molar ratio of 1:0.05, and then placed in a tube furnace and calcined at 850°C for coating. The mixture was kept warm for 15 hours to obtain the sodium ion battery positive electrode material Na3Zr2Si2PO 12 @Zr@NFM.

[0077] Example 9

[0078] The preparation method of the high-stability and high-performance sodium ion battery positive electrode material of this embodiment comprises the following steps:

[0079] (1) Combine Na2CO3, [Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ]O2 was mixed with anhydrous ethanol at a molar ratio of 0.525:1 and stirred evenly, and then the mixture was placed in a tube furnace for pre-calcination at 500°C for 5 hours; then high-temperature calcination was performed at 850°C for 15 hours, and then the NFM sample was obtained by grinding;

[0080] (2) Na2CO3, ZrO2, SiO2 and (NH4)2HPO4 were mixed in a molar ratio of 1.5:2.3:2:1, and the mixture was placed in a muffle furnace and kept at 1300°C for 8 hours, and then crushed to control the D50 to 5 μm to obtain NASICON type sodium ion conductor Zr-Na3Zr2Si2PO 12 ;

[0081] (3) NFM samples and sodium ion conductor Zr-Na3Zr2Si2PO 12 The mixture was mixed evenly at a molar ratio of 1:0.05, and then placed in a tube furnace and calcined at 850°C for coating. The mixture was kept warm for 15 hours to obtain the sodium ion battery positive electrode material Na3Zr2Si2PO 12 @Zr@NFM.

[0082] Example 10

[0083] The preparation method of the high-stability and high-performance sodium ion battery positive electrode material of this embodiment comprises the following steps:

[0084] (1) Combine Na2CO3, [Ni 1 / 3 Fe1 / 3 Mn 1 / 3 ]O2 was mixed with anhydrous ethanol at a molar ratio of 0.525:1 and stirred evenly, and then the mixture was placed in a tube furnace for pre-calcination at 500°C for 5 hours; then high-temperature calcination was performed at 850°C for 15 hours, and then the NFM sample was obtained by grinding;

[0085] (2) Na2CO3, ZrO2, SiO2 and (NH4)2HPO4 were mixed in a molar ratio of 1.5:2.3:2:1, and the mixture was placed in a muffle furnace and kept at 1300°C for 8 hours, and then crushed to control the D50 to 3 μm to obtain NASICON type sodium ion conductor Zr-Na3Zr2Si2PO 12 ;

[0086] (3) NFM samples and sodium ion conductor Zr-Na3Zr2Si2PO 12 The mixture was mixed evenly in a molar ratio of 1:0.01, and then placed in a tube furnace for high temperature calcination at 850°C for coating, and kept warm for 15 hours to obtain the sodium ion battery positive electrode material Na3Zr2Si2PO 12 @Zr@NFM.

[0087] Embodiment 11

[0088] The preparation method of the high-stability and high-performance sodium ion battery positive electrode material of this embodiment comprises the following steps:

[0089] (1) Combine Na2CO3, [Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ]O2 was mixed with anhydrous ethanol at a molar ratio of 0.525:1 and stirred evenly, and then the mixture was placed in a tube furnace for pre-calcination at 500°C for 5 hours; then high-temperature calcination was performed at 850°C for 15 hours, and then the NFM sample was obtained by grinding;

[0090] (2) Na2CO3, ZrO2, SiO2 and (NH4)2HPO4 were mixed in a molar ratio of 1.5:2.3:2:1, and the mixture was placed in a muffle furnace and kept at 1300°C for 8 hours, and then crushed to control the D50 to 3 μm to obtain NASICON type sodium ion conductor Zr-Na3Zr2Si2PO 12 ;

[0091] (3) NFM samples and sodium ion conductor Zr-Na3Zr2Si2PO 12 The mixture was mixed evenly in a molar ratio of 1:0.1, and then placed in a tube furnace for high temperature calcination at 850°C for coating, and kept warm for 15 hours to obtain the sodium ion battery positive electrode material Na3Zr2Si2PO 12 @Zr@NFM.

[0092] Example 12

[0093] The preparation method of the high-stability and high-performance sodium ion battery positive electrode material of this embodiment comprises the following steps:

[0094] (1) Combine Na2CO3, [Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ]O2 was mixed with anhydrous ethanol at a molar ratio of 0.525:1 and stirred evenly, and then the mixture was placed in a tube furnace for pre-calcination at 500°C for 5 hours; then high-temperature calcination was performed at 850°C for 15 hours, and then the NFM sample was obtained by grinding;

[0095] (2) Na2CO3, ZrO2, SiO2 and (NH4)2HPO4 were mixed in a molar ratio of 1.5:2.3:2:1, and the mixture was placed in a muffle furnace and kept at 1300°C for 8 hours, and then crushed to control the D50 to 3 μm to obtain NASICON type sodium ion conductor Zr-Na3Zr2Si2PO 12 ;

[0096] (3) NFM samples and sodium ion conductor Zr-Na3Zr2Si2PO 12 The mixture was mixed evenly at a molar ratio of 1:0.05, and then placed in a tubular furnace and calcined at 750°C for coating. The mixture was kept warm for 15 hours to obtain the sodium ion battery positive electrode material Na3Zr2Si2PO 12 @Zr@NFM.

[0097] Embodiment 13

[0098] The preparation method of the high-stability and high-performance sodium ion battery positive electrode material of this embodiment comprises the following steps:

[0099] (1) Combine Na2CO3, [Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ]O2 was mixed with anhydrous ethanol at a molar ratio of 0.525:1 and stirred evenly, and then the mixture was placed in a tube furnace for pre-calcination at 500°C for 5 hours; then high-temperature calcination was performed at 850°C for 15 hours, and then the NFM sample was obtained by grinding;

[0100] (2) Na2CO3, ZrO2, SiO2 and (NH4)2HPO4 were mixed in a molar ratio of 1.5:2.3:2:1, and the mixture was placed in a muffle furnace and kept at 1300°C for 8 hours, and then crushed to control the D50 to 3 μm to obtain NASICON type sodium ion conductor Zr-Na3Zr2Si2PO 12 ;

[0101] (3) NFM samples and sodium ion conductor Zr-Na3Zr2Si2PO 12 The mixture was mixed evenly at a molar ratio of 1:0.05, and then placed in a tube furnace and calcined at 950°C for coating. The mixture was kept warm for 15 hours to obtain the sodium ion battery positive electrode material Na3Zr2Si2PO 12 @Zr@NFM.

[0102] Embodiment 14

[0103] The preparation method of the high-stability and high-performance sodium ion battery positive electrode material of this embodiment comprises the following steps:

[0104] (1) Combine Na2CO3, [Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ]O2 was mixed with anhydrous ethanol at a molar ratio of 0.525:1 and stirred evenly, and then the mixture was placed in a tube furnace for pre-calcination at 500°C for 5 hours; then high-temperature calcination was performed at 850°C for 15 hours, and then the NFM sample was obtained by grinding;

[0105] (2) Na2CO3, ZrO2, SiO2 and (NH4)2HPO4 were mixed in a molar ratio of 1.5:2.3:2:1, and the mixture was placed in a muffle furnace and kept at 1300°C for 8 hours, and then crushed to control the D50 to 3 μm to obtain NASICON type sodium ion conductor Zr-Na3Zr2Si2PO 12 ;

[0106] (3) NFM samples and sodium ion conductor Zr-Na3Zr2Si2PO 12 The mixture was mixed evenly at a molar ratio of 1:0.05, and then placed in a tube furnace and calcined at 850°C for 10 hours to obtain the positive electrode material Na3Zr2Si2PO4 for sodium ion batteries. 12 @Zr@NFM.

[0107] Embodiment 15

[0108] The preparation method of the high-stability and high-performance sodium ion battery positive electrode material of this embodiment comprises the following steps:

[0109] (1) Combine Na2CO3, [Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ]O2 was mixed with anhydrous ethanol at a molar ratio of 0.525:1 and stirred evenly, and then the mixture was placed in a tube furnace for pre-calcination at 500°C for 5 hours; then high-temperature calcination was performed at 850°C for 15 hours, and then the NFM sample was obtained by grinding;

[0110] (2) Na2CO3, ZrO2, SiO2 and (NH4)2HPO4 were mixed in a molar ratio of 1.5:2.3:2:1, and the mixture was placed in a muffle furnace and kept at 850°C for 20 hours, and then crushed to control the D50 to 3 μm to obtain NASICON type sodium ion conductor Zr-Na3Zr2Si2PO 12 ;

[0111] (3) NFM samples and sodium ion conductor Zr-Na3Zr2Si2PO 12 The mixture was mixed evenly at a molar ratio of 1:0.05, and then placed in a tube furnace and calcined at 850°C for 20 hours to obtain the positive electrode material Na3Zr2Si2PO4 for sodium ion batteries. 12 @Zr@NFM.

[0112] Example 16

[0113] The preparation method of the high-stability and high-performance sodium ion battery positive electrode material of this embodiment comprises the following steps:

[0114] (1) Combine Na2CO3, [Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ]O2 was mixed with anhydrous ethanol at a molar ratio of 0.525:1 and stirred evenly, and then the mixture was placed in a tube furnace for pre-calcination at 500°C for 5 hours; then high-temperature calcination was performed at 850°C for 15 hours, and then the NFM sample was obtained by grinding;

[0115] (2) Na2CO3, ZrO2, SiO2 and (NH4)2HPO4 were mixed in a molar ratio of 1.8:2:2:1, and the mixture was placed in a muffle furnace and kept at 1300°C for 8 hours, and then crushed, and the D50 was controlled to be 3 μm to obtain NASICON type sodium ion conductor Na-Na3Zr2Si2PO 12 ;

[0116] (3) NFM samples and sodium ion conductor Na-Na3Zr2Si2PO 12 The mixture was mixed evenly at a molar ratio of 1:0.05, and then placed in a tube furnace and calcined at 850°C for coating. The mixture was kept warm for 15 hours to obtain the sodium ion battery positive electrode material Na3Zr2Si2PO 12 @Na@NFM.

[0117] Embodiment 17

[0118] The preparation method of the high-stability and high-performance sodium ion battery positive electrode material of this embodiment comprises the following steps:

[0119] (1) Combine Na2CO3, [Ni 1 / 3 Fe 1 / 3Mn 1 / 3 ]O2 was mixed with anhydrous ethanol at a molar ratio of 0.525:1 and stirred evenly, and then the mixture was placed in a tube furnace for pre-calcination at 500°C for 5 hours; then high-temperature calcination was performed at 850°C for 15 hours, and then the NFM sample was obtained by grinding;

[0120] (2) Na2CO3, ZrO2, SiO2 and (NH4)2HPO4 were mixed in a molar ratio of 1.5:2:2:1.3, and the mixture was placed in a muffle furnace and kept at 1300°C for 8 hours, and then crushed, and the D50 was controlled to be 3 μm to obtain NASICON type sodium ion conductor P-Na3Zr2Si2PO 12 ;

[0121] (3) NFM samples and sodium ion conductor P-Na3Zr2Si2PO 12 The mixture was mixed evenly at a molar ratio of 1:0.05, and then placed in a tube furnace and calcined at 850°C for coating. The mixture was kept warm for 15 hours to obtain the sodium ion battery positive electrode material Na3Zr2Si2PO 12 @P@NFM.

[0122] Comparative Example 1

[0123] The preparation method of the positive electrode material of the ion battery of this comparative example comprises the following steps:

[0124] (1) Combine Na2CO3, [Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ]O2 is mixed and stirred evenly in anhydrous ethanol at a molar ratio of 0.525:1, and then the mixture is placed in a tubular furnace for pre-calcination at 500°C for 3 hours; then it is calcined at a high temperature at 850°C for 15 hours, and then ground to obtain the NFM sample of the positive electrode material for the ion battery.

[0125] Comparative Example 2

[0126] The preparation method of the positive electrode material of the sodium ion battery in this comparative example comprises the following steps:

[0127] (1) Combine Na2CO3, [Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ]O2 was mixed with anhydrous ethanol at a molar ratio of 0.525:1 and stirred evenly, and then the mixture was placed in a tube furnace for pre-calcination at 500°C for 3 hours; then high-temperature calcination was performed at 850°C for 15 hours, and then the NFM sample was obtained by grinding;

[0128] (2) The NFM sample and ZrO2 were mixed evenly in a molar ratio of 1:0.005, and then placed in a tubular furnace for high-temperature calcination at 850°C for coating. The heat preservation was carried out for 15 h to obtain the sodium ion battery positive electrode material Zr@NFM.

[0129] Comparative example 3.

[0130] The preparation method of the positive electrode material of the sodium ion battery in this comparative example comprises the following steps:

[0131] (1) Combine Na2CO3, [Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ]O2 was mixed with anhydrous ethanol at a molar ratio of 0.525:1 and stirred evenly, and then the mixture was placed in a tube furnace for pre-calcination at 500°C for 3 hours; then high-temperature calcination was performed at 850°C for 12 hours, and then the NFM sample was obtained by grinding;

[0132] (2) Na2CO3, ZrO2, SiO2 and (NH4)2HPO4 were mixed in a molar ratio of 1.5:2:2:1, and the mixture was placed in a muffle furnace and kept at 1300°C for 8 hours, and then crushed, and the D50 was controlled to be 3 μm to obtain the sodium ion conductor Na3Zr2Si2PO 12 ;

[0133] (2) NFM samples and sodium ion conductor Na3Zr2Si2PO 12 The mixture was mixed evenly at a molar ratio of 1:0.05, and then placed in a muffle furnace and calcined at 850°C for coating. The mixture was kept warm for 15 hours to obtain the sodium ion battery positive electrode material Na3Zr2Si2PO 12 @NFM.

[0134] Comparative Example 4

[0135] The preparation method of the positive electrode material of the sodium ion battery in this comparative example comprises the following steps:

[0136] (1) Combine Na2CO3, [Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ]O2 was mixed with anhydrous ethanol at a molar ratio of 0.525:1 and stirred evenly, and then the mixture was placed in a tube furnace for pre-calcination at 500°C for 3 hours; then high-temperature calcination was performed at 850°C for 12 hours, and then the NFM sample was obtained by grinding;

[0137] (2) NFM samples, ZrO2 and sodium ion conductor Na3Zr2Si2PO 12The mixture was mixed evenly in a molar ratio of 1:0.005:0.05, and then placed in a muffle furnace and calcined at 850°C for coating, and kept warm for 15 hours to obtain the sodium ion battery positive electrode material Na3Zr2Si2PO 12 @Zr@NFM.

[0138] The sodium ion battery positive electrode material, conductive carbon black and PVDF binder prepared in the embodiment and the comparative example were mixed in a mass ratio of 92:4:4, and then NMP solvent was added to form a positive electrode slurry, which was then coated on an aluminum foil. After vacuum drying and rolling at 105°C, a positive electrode sheet was obtained; then the positive electrode sheet, the counter electrode sheet (metallic sodium), the electrolyte (solute NaPF6, concentration 1 mol / L, solvent EC:DEC=1:1) and the glass fiber separator were assembled into a battery, and relevant battery performance tests were carried out. The specific test method is as follows.

[0139] 1. First discharge capacity test

[0140] First, place the battery in a 25±2℃ environment for 8h, then charge it to 4.0V at 0.05C constant current, and record the resulting capacity as 0.05C charging capacity. Then, let it stand for 5min, and then discharge it to 2.0V at 0.1C constant current, and record the resulting capacity as 0.1C discharge capacity. Finally, stop running and calculate the first discharge capacity in grams according to the following formula:

[0141] First discharge capacity in grams = 0.1C discharge capacity / mass of active material.

[0142] 2. Discharge capacity test corresponding to current density of 2C

[0143] First, place the battery in a 25±2℃ environment for 8h, then charge it to 4.0V at 0.2C constant current, then let it stand for 5min, then discharge it to 2.0V at 0.2C constant current, record the capacity as C1, then let it stand for 5min, then charge it to 4.0V at 0.2C constant current, let it stand for 5min, then discharge it to 2V at 2C constant current, the obtained capacity is 2C, the corresponding discharge capacity is C2, calculate the discharge efficiency corresponding to 2C as follows:

[0144] The discharge efficiency corresponding to 2C = C2 / C1*100%.

[0145] 3. 0.5C cycle 450 cycles capacity test

[0146] First, place the battery in a 25±2℃ environment for 8h, then charge it to 4.0V at a constant current of 0.5C, then let it stand for 5min, then charge it at a constant voltage of 4.0V to a current of 0.05C, let it stand for 5min, then discharge it to 2.0V at a constant current of 0.5C, repeat the above cycle 450 times, and finally stop the operation, record the discharge capacity of the 1st and 450th cycles, and calculate the capacity retention rate of 450 cycles as follows:

[0147] 450-cycle capacity retention rate = 450th-cycle discharge capacity / 1st-cycle discharge capacity.

[0148] 4. Use a pH tester to test the pH of the positive electrode material.

[0149] The specific test results are shown in Table 1.

[0150] Table 1 Sodium ion battery performance test results

[0151] .

[0152] As shown in Table 1, it can be seen from Examples 1 to 17 that the sodium ion battery positive electrode materials prepared using the parameters within the scope of the technical solution of the present invention all have good gram capacity, discharge rate and cycle performance. Further, Example 1 Na3Zr2Si2PO prepared using the preferred parameters of the present invention 12 @Zr@NFM material has better overall effects in terms of gram capacity, discharge rate and cycle performance.

[0153] It can be seen from Examples 1, 16, and 17 that the use of a NASICON type sodium ion conductor with excess impurities on the surface to in-situ coat the positive electrode material of a sodium ion battery can use the excess impurities generated on the surface of the NASICON type sodium ion conductor as a coating agent to further coat the sodium positive electrode material to form an in-situ double coating. This double coating method has a better coating effect on the surface of the sodium positive electrode material, showing higher air stability, better rate performance, and cycle performance.

[0154] It can be seen from Examples 1 to 3 that, in the process of preparing NASICON-type sodium ion conductors, a preferred impurity ratio is used for mixing, and the prepared NASICON-type sodium ion conductor has a lower pH, so that after being simultaneously coated with NFM, the prepared positive electrode material has good rate cycling performance.

[0155] It can be seen from Examples 1, 4, and 5 that when preparing NASICON type sodium ion conductors, using a sintering temperature within the technical solution range can achieve good material properties. If the sintering temperature is too low, it will affect the Zr-Na3Zr2Si2PO 12The internal structural stability during the synthesis process affects the subsequent coating effect; if the sintering temperature is too high, Na and other elements in the material will volatilize, resulting in uneven distribution of the synthetic material, affecting the synthesis effect and also affecting the subsequent material performance.

[0156] It can be seen from Examples 1, 6, and 7 that when preparing NASICON sodium ion conductors, using a holding time within the technical solution can achieve good material properties. If the holding time is too short, Na will precipitate in Na3Zr2Si2PO 12 The precipitated Na will be introduced into the NFM sample during the coating process, resulting in poor rate and cycle performance. If the insulation time is too long, a large amount of elements will be lost, thus affecting the Na3Zr2Si2PO 12 @Zr@NFM overall performance.

[0157] It can be seen from Examples 1, 8, and 9 that the smaller the particle size obtained when preparing the NASICON type sodium ion conductor, the better the coating effect. The smaller the particle size, the more effective the coating of NFM, and the better the ionic conductivity of the material. 12 @Zr@NFM material has better rate performance and cycle performance when the pH value is reduced. 12 If it is too large, the coating effect will be poor and the ionic conductivity will be poor.

[0158] It can be seen from Examples 1, 10 and 11 that when the NASICON type sodium ion conductor is coated with the NFM sample, a better coating effect can be achieved by using the preferred ratio within the scope of the technical solution.

[0159] From Examples 1, 12, and 13, it can be seen that when the NASICON sodium ion conductor is coated with the NFM sample, the coating temperature within the scope of the technical solution can have a better coating effect, and the coating temperature can be appropriately increased to improve the NFM coating effect, reduce the pH, and improve the rate and cycle performance. If the coating temperature is too low, the coating effect will be poor, the pH will be high, and the rate and cycle performance will be poor.

[0160] It can be seen from Examples 1, 14, and 15 that when coating the NFM sample with the NASICON sodium ion conductor, using the coating and insulation time within the scope of the technical solution can achieve a better coating effect. 12 The internal structure of the material is not complete, resulting in poor rate and cycle performance. Although long-term insulation can achieve the same effect as the optimal time, excessive insulation time should be avoided for energy saving.

[0161] It can be seen from Example 1 and Comparative Examples 1 to 3 that the NFM obtained in Comparative Example 1 is not coated, and the material exhibits high gram capacity, but the high pH leads to poor rate and cycle performance; Comparative Example 2 uses ZrO2 coating alone and Comparative Example 3 uses Na3Zr2Si2PO4 without impurities. 12 Coating NFM also results in poor pH rate and cycle performance, which is far inferior to that of Na3Zr2Si2PO4 prepared in Example 1. 12 @Zr@NFM material.

[0162] It can be seen from Example 1 and Comparative Example 4 that ZrO2 and Na3Zr2Si2PO 12 The NFM was coated, but the rate and cycle performance were not as good as those of Example 1. This is because the Zr-Na3Zr2Si2PO 12 The ZrO2 can be better incorporated into the NFM and the impurity Zr is evenly dispersed in the Na3Zr2Si2PO 12 Around, it is more conducive to the coating of NFM by impurity Zr.

[0163] The various aspects, embodiments, and features of the present invention should be considered to be illustrative in all aspects and not limiting of the present invention, the scope of which is defined solely by the claims. Other embodiments, modifications, and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.

[0164] In the preparation method of the present invention, the order of each step is not limited to the order listed. For those skilled in the art, without creative work, the order of each step is also within the protection scope of the present invention. In addition, two or more steps or actions can be performed simultaneously.

[0165] Finally, it should be noted that the specific embodiments described herein are merely examples of the present invention, and are not intended to limit the implementation methods of the present invention. A person skilled in the art of the present invention may make various modifications or supplements to the specific embodiments described, or replace them in a similar manner. It is not necessary and impossible to provide all examples of all implementation methods here. However, these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention, and interpreting them as any additional limitation is contrary to the spirit of the present invention.

Claims

1. A method for preparing a highly stable and high-performance sodium ion battery positive electrode material, characterized in that: The preparation method comprises the following steps: (1) The sodium salt and the precursor are mixed and stirred in a solvent, and then the mixture is pre-calcined and high-temperature calcined, and then ground to obtain the NFM sample; (2) After the NFM sample and the sodium ion conductor are uniformly mixed, they are coated and kept warm at high temperature to obtain a sodium ion battery positive electrode material; In the step (2), the coating temperature is 800-900°C and the insulation time is 12-18h; The sodium ion conductor is a NASICON type sodium ion conductor containing impurities M on the surface, and the general formula is M-Na 2+x Zr2Si 3- x P x O 12 , wherein M is one or more of Zr, Na, and P, and 0<x<3; The impurities M and Na in the sodium ion conductor 2+x Zr2Si 3-x P x O 12 The molar ratio is (0.1~0.5):1; The preparation method of the sodium ion conductor comprises the following steps: mixing Na2CO3, ZrO2, SiO2 and (NH4)2HPO4 according to the molar ratio in the general formula, sintering at high temperature and then crushing to obtain the sodium ion conductor M-Na 2+x Zr2Si 3-x P x O 12 ; The high temperature sintering temperature is 1300~1400℃, and the sintering time is 8~10h.

2. The preparation method according to claim 1, characterized in that: The particle size D50 of the crushed sodium ion conductor is 0.1-5 μm.

3. The preparation method according to claim 1, characterized in that: In step (1), the sodium salt includes one or more of sodium acetate, sodium nitrate, sodium carbonate, and sodium oxalate; The general formula of the precursor is [Ni 1-a-b Fe a Mn b ]O2, where 0≤a≤1, 0≤b≤1, 0≤a+b≤1; The sodium salt and the precursor are mixed and stirred at a molar ratio of the sodium element in the sodium salt to the precursor of (1-2):1; The solvent is an organic solvent, including one or more of ethanol, NMP, ether, methanol, isopropanol, and tetrahydrofuran; The pre-calcination temperature is 300-600° C., and the pre-calcination time is 1-5 hours; the high-temperature calcination temperature is 700-900° C., and the high-temperature calcination time is 10-24 hours.

4. The preparation method according to claim 1, characterized in that: In the step (2), the molar ratio of the NFM sample to the sodium ion conductor is 1:(0.01-0.1).

5. A highly stable and high-performance sodium ion battery positive electrode material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 4.

6. A high-stability and high-performance sodium ion battery positive electrode plate, characterized in that: It includes a highly stable and high-performance sodium ion battery positive electrode material as described in claim 5.

7. A high-stability and high-performance sodium ion battery, characterized in that: It includes a high-stability and high-performance sodium ion battery positive electrode plate as described in claim 6.

Citation Information

Patent Citations

  • Modified P2-type layered Mn-based oxide, preparation method thereof and application of modified P2-type layered Mn-based oxide as positive electrode material in sodium-ion battery

    CN115924977A

  • Preparation method of Na3Zr2Si2PO12 solid electrolyte

    CN116799292A